2014
DOI: 10.2174/1567205011666140812115004
|View full text |Cite
|
Sign up to set email alerts
|

Severe Psychiatric Disorders in Mid-Life and Risk of Dementia in Late- Life (Age 65-84 Years): A Population Based Case-Control Study

Abstract: Objective: To examine the association of mid-life exposure to several psychiatric disorders with the development of late-life dementia. Methods: A matched case-control study using Western Australian state-wide hospital inpatient, outpatient mental health and emergency records linked to death records. Incident dementia cases (2000-2009) aged 65 to 84 years were sex- and age-matched to an electoral roll control. Records as far back as 1970 were used to assess exposure to medical risk factors before age 65 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 62 publications
5
133
0
3
Order By: Relevance
“…In Australia, the sensitivity, positive predictive value and κ value for ICD-10 dementia diagnoses in hospital records were 67%, 76%, and 0.71, respectively, suggesting substantial agreement between medical charts and registry data [41]. We have previously demonstrated that the use of combined databases in WADLS substantially increases the detection of individuals with dementia [26,28]. In a Danish study, 86% of dementia and 81% of Alzheimer's disease diagnoses in hospital registers were correct, while the accuracy for vascular dementia was lower [42].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In Australia, the sensitivity, positive predictive value and κ value for ICD-10 dementia diagnoses in hospital records were 67%, 76%, and 0.71, respectively, suggesting substantial agreement between medical charts and registry data [41]. We have previously demonstrated that the use of combined databases in WADLS substantially increases the detection of individuals with dementia [26,28]. In a Danish study, 86% of dementia and 81% of Alzheimer's disease diagnoses in hospital registers were correct, while the accuracy for vascular dementia was lower [42].…”
Section: Discussionmentioning
confidence: 93%
“…Dementia case and comorbidity ascertainment All hospital admissions, contacts with mental health services and deaths in Western Australia are recorded in the WADLS [25], and the combination of databases has been shown to improve the identification of individuals with dementia [26][27][28]. The WADLS was used to determine prevalent dementia status at study entry from ICD coding from 1982 and incident dementia to the end of June 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 These findings indicate that both neurobiological and environmental factors could contribute to the excess risk of dementia in persons with schizophrenia. Four previous longitudinal studies identified a total of 196 persons with schizophrenia who developed a clinical dementia diagnosis [15][16][17][18] ; the studies found relative risks for the development of dementia ranging from 2.4 to 16. As the median age at onset is 28 years for schizophenia 19 and 81 years for size and follow-up time to include all persons with schizophrenia and allow for a sufficient induction period between a diagnosis of schizophrenia and a diagnosis of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Four prior studies have compared the risk of dementia among persons with vs those without schizophrenia using clinical dementia diagnoses, and their findings ranged from a 2.4-fold to a 16-fold higher risk of developing dementia. [15][16][17][18] However, those studies were limited because they did not include individuals with onset of schizophrenia before the age of 30 years [16][17][18] (potentially effecting generalizability, as the majority of persons with schizophrenia are diagnosed before the age of 30 years 19 ) or had an insufficient duration of follow-up for the cohort to display a clinically significant risk of developing dementia. 15 Furthermore, a recent review of 20 longitudinal studies using cognitive screening tools or neuropsychological tests to examine the risk of cognitive decline (ie, beyond what can be attributed to the pathophysiologic factors of schizophrenia itself) in persons with schizophrenia found inconsistent results: 12 studies suggested significant cognitive decline, whereas 8 studies did not find a significant association.…”
mentioning
confidence: 99%